Kajian Peraturan dan Persepsi Konsumen tentang Pencantuman Klaim Natrium Pada Pangan Olahan Antara - Prahasti, Gita Eka; Kusnandar, Feri; Palupi, Nurheni Sri (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2025)
Excessive salt intake is a major risk factor for hypertension and cardiovascular disease, and reducing consumption is an effective strategy to mitigate this health concern. Salt intake is regulated through various government policies, including BPOM Regulation Number 1 of 2022, which outlines general requirements for nutritional content claims on processed foods, including those related to sodium levels and comparative statements. This study had three main objectives: (1) to compare regulations on low-sodium claims for processed foods across different countries and Codex standards; (2) to identify processed foods with low-sodium claims currently available in the Indonesian market; and (3) to evaluate consumer perceptions of processed foods carrying such claims. Regulations in Indonesia, Malaysia, Singapore, Thailand, Europe, the United States, Australia, New Zealand, and Codex permit sodium content claims across all food product categories, including intermediate processed foods, provided that the specific requirements of each jurisdiction are met. In Indonesia, intermediate processed foods such as seasonings and cooking sauces that bear sodium content claims and have obtained distribution permits are already available in the market. The presence of sodium-related claims has been shown to significantly and positively influence consumer perceptions and purchasing behavior. Survey results further revealed that consumers recognize variability in the amount of salt they consume from different processed food products.